2011
DOI: 10.1889/jsid19.6.453
|View full text |Cite
|
Sign up to set email alerts
|

Review Paper: Progress on efficient cathodes for organic light‐emitting diodes

Abstract: Abstract— Balanced charge injection is essential for highly efficient and stable OLEDs. Various cathode materials, such as elemental metals, metal alloys, and metal compounds, have been adopted to facilitate electron injection. Currently, composite cathodes utilizing an electron‐injection layer and an air‐stable metal, such as LiF/Al, is the most common choice. This article will review the progress of efficient vacuum‐evaporated cathodes for OLEDs and their mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…Titanium dioxide (TiO 2 ), with a small conduction band offset with silicon , and low work‐function materials as lithium fluoride (LiF) , magnesium fluoride (MgF 2 ) , and cesium carbonate (CsCO 3 ) have been demonstrated to be efficient electron‐selective contacts for silicon solar cells. Compared with doped‐silicon‐layer‐based CSCs that involve complex deposition conditions with toxic gases and may lead to undesired optical losses , these dopant‐free CSCs, are easily deposited, potentially at low cost, by thermal evaporation, atomic layer deposition (ALD), spin‐coating, brush painting, and even printing, as widely demonstrated by organic solar cells and light‐emitting diodes . Moreover, these wide‐bandgap, dopant‐free CSCs are broadband transparent, making them more suitable as window layers for silicon solar cells than doped silicon layers, which suffer from parasitic absorption losses in the blue wavelength range.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ), with a small conduction band offset with silicon , and low work‐function materials as lithium fluoride (LiF) , magnesium fluoride (MgF 2 ) , and cesium carbonate (CsCO 3 ) have been demonstrated to be efficient electron‐selective contacts for silicon solar cells. Compared with doped‐silicon‐layer‐based CSCs that involve complex deposition conditions with toxic gases and may lead to undesired optical losses , these dopant‐free CSCs, are easily deposited, potentially at low cost, by thermal evaporation, atomic layer deposition (ALD), spin‐coating, brush painting, and even printing, as widely demonstrated by organic solar cells and light‐emitting diodes . Moreover, these wide‐bandgap, dopant‐free CSCs are broadband transparent, making them more suitable as window layers for silicon solar cells than doped silicon layers, which suffer from parasitic absorption losses in the blue wavelength range.…”
Section: Introductionmentioning
confidence: 99%
“…Low work function metal alloy cathodes, such as Mg:Al, 4 are susceptible to atmospheric conditions. 56 Therefore, for increased stability, cathode bilayer structures, such as MgAg/Ag 14,57 and LiF/Al, 56,58,59 have been frequently used. Numerous other studies have investigated n-type metal oxide semiconductors 60 and alkali metal containing interlayers.…”
Section: Cathode and Electron Injection Layer (Eil)mentioning
confidence: 99%
“…The metallic cesium mechanism reveals that Cs 2 CO 3 has a superior electron injection ability regardless of the cathode metal [25]. Duan et al indicated that Cs 2 CO 3 with low evaporation temperatures would decompose and release low work function metal Cs during evaporation, enabling promising electron injection for OLEDs [26]. The enhanced electron injection is associated with a strong n-doping effects and increase of electron concentrations in the ETL induced by Cs 2 CO 3 .…”
Section: Temperature Dependent Electroluminescence (El) Of Cs 2 Co 3 mentioning
confidence: 99%